Vidia and the fairy crown - Clarke, Judith (TOKYOPOP, 2008)
When Vidia, a disagreeable fairy, finds herself accused of stealing the Queen's tiara, she enlists the aid of a fellow sprite to help investigate and the two race against time to clear Vidia's name.